Rikoksen valmistelun kriminalisoimisen perusteluista ja ongelmista - Pöyhönen, Pekka (Helsinki Law Review, 2012)
Conversation on whether preparing a severe crime, such as murder or robbery, should be criminalized has risen during the past years. This is mainly due to the school shootings in Jokela in 2007 and Kauhajoki in 2008, as well as the attempted robbery on an armored car in Lieto in 2007. Traditionally, the Finnish legislator has refrained from criminalizing acts of preparation, only quite exceptionally reaching the boundaries of punishability to conduct prior to attempt. The Government Programme of Prime Minister Jyrki Katainen’s government, however, does include an objective of criminalizing the preparation for severest crimes. In this context, a body of experts set by the Ministry of Justice late 2011, gave their suggestion for the Government Proposal on the matter on the 29th of March 2012. The suggestion proposes criminalizing preparation for homicide, aggravated assault, aggravated robbery and hostage taking. This article aims to provide an idea of how the Criminal Law in Finland currently reacts to the different chronological stages in the process of committing a crime. I first enlighten problems typical to locating the interfaces between these stages, focusing especially on the problem of determining the starting point of criminal preparation. To further clarify the subject in question, a I give a brief description on how preparation for criminal conduct is criminalized in Sweden, Norway and Denmark, all of which differ from one another regarding how the issue has been legislated. I carry on by contemplating on different angles of reasoning presented in favor of such criminalizations and outline the general criteria for any new criminalization in Finland, as well as their relation to the specific subject of the article. Emphasis is given to the nulla poena sine lege principle. In the spirit of the principle of ultima ratio, I present some possible alternatives to new criminalizations. The conclusion is that there indeed appears to be a call for criminalizing some acts of preparation. However, it is also evident that various challenges arise from implementing a somewhat novel institution into the Finnish system of criminal law. The legislator must take these challenges carefully into account.